Normalized Synergy Predicts That CD8 Co-Receptor Contribution to T Cell Receptor (TCR) and pMHC Binding Decreases As TCR Affinity Increases in Human Viral-Specific T Cells - Williams, Chad M.; Schonnesen, Alexandra A.; Zhang, Shu-Qi; Ma, Ke-Yue; He, Chenfeng; Yamamoto, Tori; Eckhardt, S. Gail; Klebanoff, Christopher A.; Jiang, Ning (Frontiers in Immunology, 2017)
The discovery of naturally occurring T cell receptors (TCRs) that confer specific, high affinity recognition of pathogen and cancer-associated antigens remains a major goal in cellular immunotherapies. The contribution of the CD8 co-receptor to the interaction between the T cell receptor (TCR) and peptide-bound major histocompatibility complex (pMHC) has previously been correlated with the activation and responsiveness of CD8+ T cells. However, these studies have been limited to model systems of genetically engineered hybridoma TCRs or transgenic mouse TCRs against either a single epitope or an array of altered peptide ligands. CD8 contribution in a native human antigen-specific T cell response remains elusive. Here, using Hepatitis C Virus specific precursor CTLs spanning a large range of TCR affinities, we discovered that the functional responsiveness of any given TCR correlated with the contribution of CD8 to TCR/pMHC binding. Furthermore, we found that CD8 contribution to TCR/pMHC binding in the two-dimensional (2D) system was more accurately reflected by normalized synergy (CD8 cooperation normalized by total TCR/pMHC bonds) rather than synergy (total CD8 cooperation) alone. While synergy showed an increasing trend with TCR affinity, normalized synergy was demonstrated to decrease with increase of TCR affinity. Critically, normalized synergy was shown to correlate with CTL functionality and peptide sensitivity, corroborating three-dimensional (3D) analysis of CD8 contribution with respect to TCR affinity. In addition, we identified TCRs that were independent of CD8 for TCR/pMHC binding. Our results resolve the current discrepancy between 2D and 3D analysis on CD8 contribution to TCR/pMHC binding, and demonstrate that naturally occurring high affinity TCRs are more capable of CD8 independent interactions that yield greater functional responsiveness even with CD8 blocking. Taken together, our data suggest that addition of the normalized synergy parameter to our previously established TCR discovery platform using 2D TCR affinity and sequence test would allow for selection of TCRs specific to any given antigen with the desirable attributes of high TCR affinity, CD8 co-receptor independence and functional superiority. Utilizing TCRs with less CD8 contribution could be beneficial for adoptive cell transfer immunotherapies using naturally occurring or genetically engineered T cells against viral or cancer-associated antigens.